Environmental risks and resource potential in small-scale gold mine tailings: A case study of Camarines Norte and Benguet, Philippines - Gibaga, Cris Reven L.; Samaniego, Jessie O.; Tanciongco, Alexandria M.; Quierrez, Rico Neil M.; Gervasio, John Henry C; Bautista VII, Angel T. (Journal of Degraded and Mining Lands Management, 2026)
The tailings from the small-scale gold mining (SSGM) process are considered an environmental risk despite still containing precious metals. The tailings from three (3) small-scale mining sites, namely Paracale-Gumaus, Thanksgiving, and Antamok, were evaluated for both their environmental risk index as well as the amount of metals that are present. Results indicate that the tailings from the Paracale-Gumaus area have higher amounts of Au and Ag content at 26.9 mg/kg and 65.6 mg/kg, respectively, while having high amounts of mercury, arsenic, lead, and zinc. The Thanksgiving tailings, on the other hand, have low amounts of precious metals (Au: 2.9 mg/kg; Ag: 9.1 mg/kg) but have the highest environmental risk due to the presence of Cd. On the other hand, the Antamok tailings have relatively less contaminated levels, though there is an enrichment in potentially toxic elements (PTEs). The findings show the importance of adopting an approach to SSGM tailings management that involves risk mitigation alongside sustainable recovery processes, such as the use of green extraction techniques, which could lead to more effective recovery processes without causing much environmental damage. The findings clearly show that SSGM tailings can be categorized as resource-oriented, risk-oriented, or both. These findings serve as a foundation for classifying the SSGM tailings that will be remediated or recovered in the Philippines and other regions where artisanal mining takes place.